Classroom Action Research: What Are Mathematics Teachers’ Problems in the Implementation? - Nur Izzati; Rindi Antika; Alona Dwinata (Jurnal Gantang, 2023)
This study aims to describe the problems of mathematic teachers in doing classroom action research (CAR). Specifically, this study aims to: (1) Describe the problem of mathematics teachers in planning, implementing, and making reports on the results of classroom action research; (2) Describe the factors causing the problems of mathematics teachers in planning, implementing, and making reports on the results of classroom action research. The study applied a descriptive method. The samples were civil servant mathematics teachers who served in several State Junior High Schools, State High Schools, and State Vocational Schools in Tanjung Pinang City. Data were collected through questionnaires, interviews, and documentation. Data were analyzed and presented descriptively. Some of them were caused by: 1) being busy; 2) difficulty getting literature; 3) Lack of technology mastery; 4) the CAR training could be more optimal.